Maturation of overy,embryonic and post-embryonic larval development of macrobrachium canarae (TIWARI,1958) - Sandhya, K. S. (KUFOS, 2013)
Abstract- M. canarae (Tiwari, 1958) is a medium sized prawn which has been reported to occur widely throughout the Kerala. The present study is on the reproductive biology of the species such as the determination of maturity stages based on the external observation, time taken for transforming to different maturity stages, breeding behavior, embryonic development, larval development and the importance of the species as a candidate species for aquarium.